Renewable Energies and Low-Carbon Society: Application of CGE Model to Toyohashi City in Japan - Yuzuru Miyata; Shuai Han (European Regional Science Association (ERSA), 2010)
Reducing CO2 emissions is the most significant target in the global environmental issue. One of strongest measures for CO2 reduction may be introduction of renewable energies including wind and solar powers. Moreover smart grid is attracting attention as a new power supply system for CO2 reduction as well. Integration of renewable energies, smart grid and eco-friendly vehicles could significantly reduce CO2 emissions leading to the Low-Carbon Society. However economic assessment has not been implemented for such an attractive social form without a few exceptional studies. Thus this article aims to examine the economic performance of Low-Carbon Society taking Toyohashi city in Japan as a study region. The methodology applied in this article is a static CGE model. In this model, renewable energies, smart grid and eco-friendly vehicles are incorporated in addition to the standard structure of a CGE model. Toyohashi city will be evaluated from the viewpoint of reductions in CO2 emissions and fossil fuel consumption, and welfare level by employing the equivalent variation.
Keywords: 330